Application of the Generalized Molar‐Ratio Method to the Determination of the Stoichiometry and Apparent Binding Constant of Nanoparticle‐Organic Capping Systems. Issue 10 (30th June 2015) - Doménech‐Carbó, Antonio; González‐Béjar, María; Pérez‐Prieto, Julia
Abstract A generalization of the molar‐ratio method is applied to the determination of the stoichiometry and apparent binding constant of metal nanoparticle‐organic capping complexes (MmLx) using voltammetric data for the oxygen reduction reaction (ORR) in air‐saturated aqueous phosphate buffer solutions. The method is applied to the formation of binary nanohybrids consisting of gold nanoparticles (AuNPs) capped with a rigid spacer, cucurbit[7]uril (CB), termed AuNP@CB, as well as to the formation of their ternary complexes (MmLxBz) with methylene blue (MB), termed AuNP@CB@MB. The obtained stoichiometries correspond to binding of four Au surface atoms for each CB unit.